Equity and the willingness to pay for green electricity in Germany. (October 2018) - Andor, Mark; Frondel, Manuel; Sommer, Stephan
Abstract The production of electricity on the basis of renewable energy technologies is often discriminatively financed: the German energy-intensive sector, for instance, benefits from a far-reaching exemption rule, while all other electricity consumers are forced to bear a higher burden in the form of a higher surcharge on the net price of electricity. Here, we demonstrate that reducing this inequity in cost burden substantially raises household willingness to pay for green electricity. In a stated-choice experiment among about 11, 000 households, participants who were informed about the energy industry exemption were less likely to accept an increase in the fixed surcharge per kilowatt hour than those who were not informed. However, participants who were informed about the industry exemption but then told that it would be abolished had significantly higher acceptance rates. This suggests that reducing inequity in the distribution of the cost burden increases the acceptance of bearing these costs. This outcome may have far-reaching implications for policymaking that extend to other domains where exemptions exist, such as carbon tax schemes. The cost of green electricity is unfairly distributed, with consumers paying more while industry actors are subsidized. Here, the authors find that reducing the inequity in cost burden by abolishing exemptions increases consumer acceptance of these costs.